(untitled) (Comillas Journal of International Relations, 2019)
Asia and the Pacific have traditionally been forgotten areas of the Spanish foreign policy. However, in the last twenty years the Spanish government has shown a new interest in this area, translated into the preparation of several action plans, the creation of various bilateral forums, and the increase of political, economic, cultural and cooperation relations. In this context, in addition to China, India, Korea and Japan, has highlighted the new importance that has been granted to the Philippines, a Spanish colony for more than three hundred years. It is not easy to reestablish relations with an old colonial territory with which ties were broken many decades ago. However, a remarkable effort has been made to define new bases on which sustain relations, enhance the issues that still unite us, and determine the strong areas for collaboration. From this perspective, this paper carries out an analysis of the new relations established with Asia in general and with the Philippines in particular during the governments of the democratic era.